2011
DOI: 10.1021/bi200168n
|View full text |Cite
|
Sign up to set email alerts
|

Dioxygen Transmembrane Distributions and Partitioning Thermodynamics in Lipid Bilayers and Micelles

Abstract: Cellular respiration, mediated by the passive diffusion of oxygen across lipid membranes, is key to many basic cellular processes. In this work, we report the detailed distribution of oxygen across lipid bilayers and examine the thermodynamics of oxygen partitioning via NMR studies of lipids in a small unilamellar vesicle (SUV) morphology. Dissolved oxygen gives rise to paramagnetic chemical shift perturbations and relaxation rate enhancements, both of which report on local oxygen concentration. From SUVs cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 79 publications
(158 reference statements)
6
16
0
Order By: Relevance
“…These profiles demonstrate that O 2 and NO spontaneously partition into the membrane from the aqueous solution by first overcoming a small free energy barrier of only 0.5 kcal/mol located in the polar head group region, followed by favorable penetration into the lipid tail region, and finally settle largely near the midpoint of the bilayer corresponding to the global minimum of −2 to −1.5 kcal/mol. These results are consistent with those from obtained from fluorescence, NMR, and ESR experimental studies [2224] and with those from previous simulations using free energy methods (e.g., ILS and umbrella sampling) [80, 9498], establishing that small, hydrophobic gases are 5–10 fold more soluble in the membrane than in the aqueous solution. The location of the global minimum allows for O 2 and NO molecules to readily migrate between upper and lower membrane leaflets, a characteristic that will be contrasted by larger amphipathic molecules described in later sections.…”
Section: Lipid Mediated Essential Functions Of Gases In Membrane Protsupporting
confidence: 91%
See 1 more Smart Citation
“…These profiles demonstrate that O 2 and NO spontaneously partition into the membrane from the aqueous solution by first overcoming a small free energy barrier of only 0.5 kcal/mol located in the polar head group region, followed by favorable penetration into the lipid tail region, and finally settle largely near the midpoint of the bilayer corresponding to the global minimum of −2 to −1.5 kcal/mol. These results are consistent with those from obtained from fluorescence, NMR, and ESR experimental studies [2224] and with those from previous simulations using free energy methods (e.g., ILS and umbrella sampling) [80, 9498], establishing that small, hydrophobic gases are 5–10 fold more soluble in the membrane than in the aqueous solution. The location of the global minimum allows for O 2 and NO molecules to readily migrate between upper and lower membrane leaflets, a characteristic that will be contrasted by larger amphipathic molecules described in later sections.…”
Section: Lipid Mediated Essential Functions Of Gases In Membrane Protsupporting
confidence: 91%
“…Common gases such as O 2 , NO and CO 2 congregate in lipid membranes [1924], and reach their target sites within membrane-embedded proteins in rapid fashion, presumably by the existence of protein tunnels leading from the membrane core [2528]. Additionally, contemporary pharmaceuticals and drug-like signaling molecules often depend on partitioning into the membrane to find their binding target, approximately ~ 60% of which are membrane-associated [29].…”
Section: Membrane Activity Is a Critical Factor In The Biology Of Smamentioning
confidence: 99%
“…A glutamate mutation at position 272 was chosen because its side chain can extend farther into the cavity than that of leucine, despite its slightly smaller total volume. Such a projection will diminish the local hydrophobicity and influence the rate of dioxygen migration through that region of the protein (25). These anticipated structural and polarity changes suggested that the T201 peroxo formation rate would decrease if L272 were on the O 2 migration pathway.…”
Section: Resultsmentioning
confidence: 99%
“…The variants were designed primarily based on size rather than hydrophobicity with the assumption that steric bulk and the attendant alterations in the volume of the pathways are most critical for controlling O 2 access (24). Two mutations, however, were designed to probe hydrophobicity as well as the size of the amino acids because a polar residue may contribute to the slower rate of dioxygen transfer (25). In the experiments described here, a T201S mutation was introduced to provide a sensor, in the form of an optical transition at 675 nm (17), to detect dioxygen arrival at the diiron sites via formation of the T201 peroxo intermediate.…”
mentioning
confidence: 99%
“…Almeida and co-workers 150 assessed two cyclen-derived Gd(III) complexes as possible PRE-inducing probes, aiming at applications for studies of protein-protein interactions. Al-Abdul-Wahid et al 151 studied the topology and immersion debth of an integral membrane protein using the PRE caused by dissolved oxygen gas. Two papers have dealt with methodological aspects of protein labelling with nitroxide.…”
Section: Paramagnetic Systems In Solutionmentioning
confidence: 99%